Platelet reactivity in patients with aortic stenosis depends on LV-AO angle. (25th November 2020) - Mourikis, P; Zako, S; Dannenberg, L; M'Pembele, R; Hohlfeld, T; Zeus, T; Kelm, M; Veulemans, V; Polzin, A
Abstract: Background: The pathogenesis of aortic stenosis (AS) is not fully understood. However, local inflammation of the valve appears to be a main player. Except haemostasis, platelets contribute to inflammatory processes in various ways. Furthermore, platelet function is altered in patients with AS. Moreover, a steep angle between the left ventricle and the aorta (LV-AO-angle) leads to turbulent blood flow. However, it is not known if platelet reactivity is associated with steep LV_AO angle in patients with AS. Methods: We included 289 patients with severe AS and performed cardiac computertomography to assess the LV-AO-angle. Platelet function was evaluated by light transmission aggregometry by using collagen and adenosine-diphosphate to induce platelet activation Results: ADP- and collagen induced aggregation showed a significant negative correlation with LV-AO-angle (ADP: r=−0.19, p=0.0009, R 2 =0.022; collagen: r=−0.21, p=0.0004, R 2 =0.027). ADP-induced MoA was significant higher in patients with a LV-AO-angle <160° in comparison to patients with an angle ≥160° (<160°: 66.99±20.72% vs. ≥160°: 60.66±19.85%, p=0.009). Collagen-induced platelet reactivity was significant higher in patients with a LV-AO-angle <160° in comparison to patients with an angle ≥160° (<160°: 78.67±13.19% vs. ≥160°: 73.85±14.44%, p=0.003). Multivariate cox-regression revealed that LV-AO angle <160 was a robust predictor of ADP- and collagen-induced platelet aggregation Conclusion: A steep LV-AO-angle is associated with enhanced platelet reactivity in patients with AS. Platelet activation is known to lead to local inflammation. Therefore, enhanced platelet reactivity could play crucial in the progression of AS. The clinical significance of a steep LV-AO-angle needs be evaluated in further trials. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): German Research Foundation